DEVELOPMENT OF A PRE MARITAL EDUCATION MODEL FOR BRIDE AND GROOM CANDIDATES AT THE OFFICE OF RELIGIOUS AFFAIRS (KUA) PADANG BOLAK - Daud; Zulhimma; Zainal Efendi Hasibuan, (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to develop a Pre-Marital Education Model for prospective brides and grooms at the Office of Religious Affairs (KUA) Padang Bolak. The purpose of the model is to enhance the readiness of couples in facing marital life and to promote the establishment of sakinah, mawaddah, and rahmah families based on Islamic values. The research employs the Research and Development (R&D) method adapted from the Borg and Gall model, consisting of seven main stages: needs analysis, planning, product development, expert validation, revision, limited field trials, and final product refinement. Data were collected through expert validation sheets, observation, questionnaires, and interviews, then analyzed using quantitative and qualitative descriptive techniques. The validation results showed high feasibility, with average expert ratings of 90% (content), 92% (design), 96% (language), and 90% (implementation). The trial results indicated that the model is valid, practical, and effective in improving participants’ understanding, communication skills, and emotional readiness for marriage. This study concludes that the developed pre-marital education model can be effectively implemented as an innovative framework for family education at KUA. It contributes to strengthening Islamic marriage preparation programs and supports the government’s efforts to reduce divorce rates through comprehensive pre-marital guidance.